ANALISIS KESALAHAN PENGGUNAAN EJAAN PADA POSTINGAN MEDIA SOSIAL INSTAGRAM @FASILKOM.UPNVJATIM - Lina Rhomaningtias; Salsabila Wardah; Adenda Khairunisa; M. Wildan Maulidan; Taswirul Afkar (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study was conducted to analyze spelling errors in social media posts on Instagram account @fasilkom.upnvjatim. The method used is descriptive qualitative analysis, where data is collected through direct observation of various captions posted. The most common spelling mistakes on the @fasilkom.upnvjatim Instagram account include improper capitalization, punctuation errors, and the use of words that are not in accordance with the rules. The results of the analysis show that of the 10 posts studied, there were 15 spelling errors, with 10 errors in word writing, 3 in the use of letters, and 2 in punctuation. Although the number of errors is relatively small, the impact on the credibility and effectiveness of digital communication is significant. To improve the quality of communication, it is recommended to implement editorial standards as well as training social media managers on the Indonesian General Spelling Guidelines (PUEBI).